Temperature Profiles and Thermal Properties of the Ground in Cyprus, for Use in the Design of Ground Heat Exchangers - Florides, Georgios A.; Pouloupatis, Panayiotis; Kalogirou, Soteris A.; Messaritis, Vassilios; Panayides, Ioannis; Zomeni, Zomenia; Partasides, George; Lizides, Andreas; Sophocleous, Eleni; Koutsoumpas, Kostas (My University, 2010)
The objective of this project is to investigate and determine the geothermal parameters of the ground in Cyprus, for use in the design of ground heat exchanger applications and ground thermal storage. Especially for the case of Cyprus, warm climate and the mild weather conditions in relation to other countries, provide a valuable set of conditions for the development of such energy systems. One of the specific objectives of the project is to investigate and accurately define the ground thermal properties in Cyprus so as to provide all interested in this technology, with actual ground data. Such information is currently unavailable. Different kinds of geological structures are being investigated as well. Subsequently, neural networks will be used for the generation of geothermal maps that will show the temperature distribution at 3 different depths. In this way and for the first time, the geographical area of Cyprus will be covered and valid data will be available. The purpose of this paper is to report the information collected at six representative sites of Cyprus and prepare a map depicting the thermal characteristics of the ground in Cyprus.
Keywords: Ground thermal behaviour; Ground temperature; Ground heat exchangers; Ground thermal applications